Bioactive Glass-Enhanced Resins: A New Denture Base Material - Raszewski, Zbigniew; Chojnacka, Katarzyna; Mikulewicz, Marcin; Alhotan, Abdulaziz (Materials, 2023)
BACKGROUND: The creation of the denture base material with bioactive properties that releases ions and produces hydroxyapatite. METHODS: Acrylic resins were modified by the addition of 20% of four types of bioactive glasses by mixing with powders. Samples were subjected to flexural strength (1, 60 days), sorption and solubility (7 days), and ion release at pH 4 and pH 7 for 42 days. Hydroxyapatite layer formation was measured using infrared. RESULTS: Biomin F glass-containing samples release fluoride ions for a period of 42 days (pH = 4; Ca = 0.62 ± 0.09; P = 30.47 ± 4.35; Si = 22.9 ± 3.44; F = 3.1 ± 0.47 [mg/L]). The Biomin C (contained in the acrylic resin releases (pH = 4; Ca = 41.23 ± 6.19; P = 26.43 ± 3.96; Si = 33.63 ± 5.04 [mg/L]) ions for the same period of time. All samples have a flexural strength greater than 65 MPa after 60 days. CONCLUSION: The addition of partially silanized bioactive glasses allows for obtaining a material that releases ions over a longer period of time. CLINICAL SIGNIFICANCE: This type of material could be used as a denture base material, helping to preserve oral health by preventing the demineralization of the residual dentition through the release of appropriate ions that serve as substrates for hydroxyapatite formation.